Federated Learning Resource Optimization and Client Selection for Total Energy Minimization Under Outage, Latency, and Bandwidth Constraints With Partial or No CSI - Mohamed Hany Mahmoud; Abdullatif Albaseer; Mohamed Abdallah; Naofal Al-Dhahir (IEEE Open Journal of the Communications Society, 2023)
We consider the problem of minimizing the total energy consumption due to the computation and communication tasks of federated learning (FL) under bandwidth and latency constraints. To avoid channel state information (CSI) feedback to the transmitter, we adopt outage probability as an additional constraint in the energy minimization problem. First, we define a feasibility metric based on the system design parameters to exclude slow clients (stragglers). Then, we propose a novel client selection algorithm, after excluding stragglers, based on dividing the remaining clients into clusters, where clients within the same cluster collaborate in a communication round to train their local models. For each communication round, one client cluster is selected in a round-robin fashion. Furthermore, we formulate and solve a resource allocation problem to optimize the transmit power, clock frequency, allocated bandwidth, and communication latency of clients within each cluster to minimize the total energy subject to total bandwidth, latency, and outage constraints. Moreover, we extend our FL design framework to the case of no CSI at both the client and server ends using differential transmission to eliminate CSI estimation pilot overhead and complexity at comparable total energy consumption and learning accuracy to coherent transmission. We test our proposed algorithms over MNIST and Fashion-MNIST datasets in iid and non-iid settings. Our proposed client selection algorithm reduces the number of participating clients per communication round by 41% compared to the baseline while maintaining the same learning accuracy. Moreover, our results demonstrate that increasing the number of receive antennas at the server from one to four can reduce the number of communication rounds required to reach a predetermined testing accuracy level by up to 53% for the Fashion-MNIST dataset.